Identifying Critical Infrastructure for Local Economic Development in Rapidly Growing Small Towns - Febrayanto, Catur Raharjo; Susiyanti, Fitri; Yulianto, Mohammad Agus; Nugraha, Muhammad Siwi; Hirbasari, Ira Amanda; Hanfan, Ahmad; Isni, Lusiana Indira (Universitas Muhammadiyah Ponorogo, 2025)
Brebes Regency, Indonesia, exhibits significant economic growth but also the highest poverty rate in Pekalongan Residency, indicating uneven development. This study identifies local economic potential and prioritizes infrastructure needs for sustainable economic growth in rapidly developing small towns within Brebes Regency, Indonesia. Data were collected through Focus Group Discussions (FGDs) and supplemented by secondary data from relevant Local Government Agencies (OPDs), providing insights on existing infrastructure, potential economic activities, and necessary facilities for local development. The analysis utilized qualitative descriptive methods, regression to assess economic growth trends, and Klassen's typology to classify economic activities. Findings indicate significant opportunities in key sectors such as agriculture and fisheries, highlighting the urgent need for targeted infrastructure investments, including rice mills, fish hatcheries, and vocational training centers, to bolster these sectors. The study concludes that strategic infrastructure development, informed by both primary and secondary data sources, is essential for maximizing economic potential and fostering sustainable growth in Brebes Regency's small towns. This research supports informed policy decisions regarding resource allocation and infrastructure planning, contributing to equitable development and enhanced economic resilience in the region.